Capital and labor taxes with costly state contingency - Alex Clymo; Andrea Lanteri; Alessandro T. Villa (Federal Reserve Bank of Chicago, 2022)
We analyze optimal capital and labor taxes in a model where (i) the government makes noncontingent announcements about future policies and (ii) ex-post statecontingent deviations from these announcements are costly. With Full Commitment, optimal fiscal announcements are unbiased forecasts of future taxes. Costly state contingency dampens the response of both current and future capital taxes to government spending shocks, because the government uses announcements about future taxes to stimulate current output. Labor taxes play a major role in accommodating fiscal shocks. This mechanism allows the model to successfully match the empirical volatility of tax rates. In the absence of Full Commitment, optimal fiscal announcements are strategically biased. Costly state contingency generates an endogenous degree of fiscal commitment, leading to a positive, but low average capital tax-approximately 8% in our calibrated model.
Keywords: 330; Optimal Fiscal Policy; Fiscal Announcements; Costly State Contingency; Time Inconsistency